2021
DOI: 10.1038/s41598-021-02825-8
|View full text |Cite
|
Sign up to set email alerts
|

Response triggering by an acoustic stimulus increases with stimulus intensity and is best predicted by startle reflex activation

Abstract: In a simple reaction time task, the presentation of a startling acoustic stimulus has been shown to trigger the prepared response at short latency, known as the StartReact effect. However, it is unclear under what conditions it can be assumed that the loud stimulus results in response triggering. The purpose of the present study was to examine how auditory stimulus intensity and preparation level affect the probability of involuntary response triggering and the incidence of activation in the startle reflex ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Since the measurement channel for the M1 had low specificity in this study, further confirmation is still needed. Furthermore, as suggested by other researchers ( Carlsen et al, 2003 ; Carlsen and Maslovat, 2019 ; Maslovat et al, 2021 ), using SCM + as a marker of successful induction of the SE should be considered in future studies.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Since the measurement channel for the M1 had low specificity in this study, further confirmation is still needed. Furthermore, as suggested by other researchers ( Carlsen et al, 2003 ; Carlsen and Maslovat, 2019 ; Maslovat et al, 2021 ), using SCM + as a marker of successful induction of the SE should be considered in future studies.…”
Section: Discussionmentioning
confidence: 89%
“…This phenomenon is called the StartleReact effect (SE) and is recognized as the result of the rapid transmission of motion commands mainly via the RST ( Carlsen and Maslovat, 2019 ). Despite not always occurring simultaneously ( Leow et al, 2018 ), early activation of the sternocleidomastoid muscle (SCM) due to the startle reflex is strongly correlated with early initiation of movement in this paradigm ( Maslovat et al, 2021 ). The SCM activation latency in the time window of 30 to 130 ms provides a convenient marker of the SE ( Carlsen et al, 2011 ; van Lith et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, when a loud acoustic stimulus also elicits a startle reflex (i.e. SCM +), which is an indication of activation in the reticular formation, RT reduction and the incidence of response triggering are increased relative to when no startle reflex is elicited (SCM −) 24 26 . While this does not mean that SCM − trials are devoid of reticulospinal activation, these previous results clearly show that the presence of SCM activation leads to a more robust StartReact effect that is unbiased by stimulus intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, only 20% (4/20) of participants exhibited StartReact responses in over 40% of SAS trials. While it has been reported that, on occasion, some SAS trials are triggered at a short latency without an observed startle response (SCM−), this misclassification rarely happens with a SAS of 120 dB and/or in prepared conditions (e.g., simple RT tasks) (Maslovat et al, 2021). These results suggest that in general, participants were unable to consistently prepare the probe RT task to a sufficiently high level required for a StartReact effect to be elicited.…”
Section: Discussionmentioning
confidence: 99%